Pengaruh Kualitas Pengungkapan Informasi Terhadap Volume Perdagangan Saham Dan Return Saham Studi Empiris Pada Perusahaan LQ-45 Di BEI - Maristiana Ayu (Universitas Bandar Lampung (UBL), 2013)
The influence of disclosure and time accuracy value is as an indicator to determine information expression quality degree. The completement of disclosure which has a high index and time accuracy is faster after auditing. Its give an instruction to the investors, that is a quality information. It will influence share trade volume and share return. The purpose of this research is to exam the quality of information expression toward share -trade volume and share- return at LQ-45 Company in Global Crisis Context since 2008 until 2011. The researcher conducts the supervision about the circulation of share for 10 days: 5 days before and 5 days after the expression. To analysys data in this research uses Multiple Linear Regresion Analysis Into two regression model to know the influence of Information expression quality toward share-trade volume and share-return.The result of this reearch indicates that statistically expression quality which is seen by disclosure fulfilment and time accuracy of monetary report has a siqnificant influence < 0,05 toward share-trade volume and share-return. Disclosure fulfilment influence positively toward share-trade volume. Seeing on time accuracy, expression quality which influence share-return has a siqnificant influence. On the other hand disclosure fulfilment has a negative influence toward share-return. All result indicate that information expression quality which is shown in annual report is not an important information in giving a good signal to take a decision for investors to invest, especially in global crisis context.